Fenitrothion impaired sexual behaviour and reproductive performance in male Sprague-Dawley rats - Nur Afizah Yusoff,; Mahaneem Mohamed,; Siti Balkis Budin,; Izatus Shima Taib, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Fenitrothion (FNT) induces oxidative damage in various organs including male reproductive organ such as testis and sperm; however, its effects on the male sexual behaviours and reproductive performance remain unclear. Therefore, this study aimed to evaluate the effects of FNT administration on male sexual behaviour and reproductive performance. Fertile male Sprague-Dawley rats were randomly divided into three groups (n=8/group): Control - receiving corn oil (1 mL kg-1); FNT-10 and FNT-20 receiving 10 and 20 mg kg-1 of FNT, respectively. FNT was administered via oral force feeding for 28 consecutive days prior to mating with untreated female rats. After mating, the rats were sacrificed to obtain plasma and sperm for further evaluation. Results showed that FNT-20 alone decreased AChE activity (P<0.05) compared to the control and FNT-10. Both doses of FNT also decreased sperm quality compared to control (P<0.05). A significant difference was found (P<0.05) for the presence of intromission and ejaculation among all groups. The mount and intromission latencies as well as post-ejaculation interval were increased (P<0.05) in FNT groups compared to the control group. The total mount and mount frequency were decreased (P<0.05) in FNT-10 and FNT-20 compared to the control group. For reproductive performance, there was a significant difference (P<0.05) for the mating and pregnancy indexes among all groups. Furthermore, both doses of FNT reduced the number of dams, delivered pups and male pups compared to the control (P<0.05). In conclusion, FNT impaired sexual behaviour and reproductive performance of male rats.